NILAI-NILAI EKONOMI KEWARGANEGARAAN MELALUI EDUPRENEURSHIP SEBAGAI STRATEGI PENINGKATAN KESEJAHTERAAN GURU DI INDONESIA SUATU KAJIAN TENTANG PELUANG, TANTANGAN, DAN IMPLEMENTASINYA - Tri Sutantina; Deni Zein Tarsidi; Joko Daryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to examine the economic values of citizenship through an edupreneurship approach as a strategy to improve the welfare of teachers in Indonesia. Teacher welfare is a fundamental issue in educational development, as mandated in Article 33 of the 1945 Constitution of the Republic of Indonesia, which states that the economy shall be organized as a joint effort based on the principle of kinship for the greatest prosperity of the people. This is in line with Law Number 14 of 2005 concerning Teachers and Lecturers and Law Number 20 of 2003 concerning the National Education System, which emphasize the strategic role of teachers in improving the quality of education and welfare. Edupreneurship as a form of educational innovation is seen as capable of providing new opportunities for teachers to develop entrepreneurial skills based on knowledge, creativity, and civic values oriented towards economic independence. This study uses a qualitative approach with a literature review through the analysis of various references, including scientific articles and relevant previous research reports. The results of the study show that there are three important aspects in the implementation of edupreneurship, namely: (1) opportunities, in the form of opening up space for teachers to integrate entrepreneurship into educational practices; (2) challenges, which include limited skills, policy support, and access to resources; and (3) implementation, through curriculum integration, training, and the development of collaborative networks. Thus, edupreneurship not only strengthens the economic value of citizenship, but also has the potential to improve the welfare of teachers in a sustainable manner.